Comparing diagnostic accuracy of Kato-Katz, Koga agar plate, ether-concentration, and FLOTAC for Schistosoma mansoni and soil-transmitted helminths. - Dominik Glinz; Kigbafori D Silué; Stefanie Knopp; Laurent K Lohourignon; Kouassi P Yao; Peter Steinmann; Laura Rinaldi; Giuseppe Cringoli; Eliézer K N'Goran; Jürg Utzinger (PLoS Neglected Tropical Diseases)
Background Infections with schistosomes and soil-transmitted helminths exert a considerable yet underappreciated economic and public health burden on afflicted populations. Accurate diagnosis is crucial for patient management, drug efficacy evaluations, and monitoring of large-scale community-based control programs. Methods/principal findings The diagnostic accuracy of four copromicroscopic techniques (i.e., Kato-Katz, Koga agar plate, ether-concentration, and FLOTAC) for the detection of Schistosoma mansoni and soil-transmitted helminth eggs was compared using stool samples from 112 school children in Côte d'Ivoire. Combined results of all four methods served as a diagnostic 'gold' standard and revealed prevalences of S. mansoni, hookworm, Trichuris trichiura, Strongyloides stercoralis and Ascaris lumbricoides of 83.0%, 55.4%, 40.2%, 33.9% and 28.6%, respectively. A single FLOTAC from stool samples preserved in sodium acetate-acetic acid-formalin for 30 or 83 days showed a higher sensitivity for S. mansoni diagnosis (91.4%) than the ether-concentration method on stool samples preserved for 40 days (85.0%) or triplicate Kato-Katz using fresh stool samples (77.4%). Moreover, a single FLOTAC detected hookworm, A. lumbricoides and T. trichiura infections with a higher sensitivity than any of the other methods used, but resulted in lower egg counts. The Koga agar plate method was the most accurate diagnostic assay for S. stercoralis. Conclusion/significance We have shown that the FLOTAC method holds promise for the diagnosis of S. mansoni. Moreover, our study confirms that FLOTAC is a sensitive technique for detection of common soil-transmitted helminths. For the diagnosis of S. stercoralis, the Koga agar plate method remains the method of choice.